Risk factors for laryngeal trauma and granuloma formation in pediatric intubations. (April 2018) - Jang, Minyoung; Basa, Krystyne; Levi, Jessica
Abstract: Objective: Intubation has been associated with laryngeal injury that often resolves spontaneously without complication. We present a case of a child intubated for less than 48 hours, who presented with dysphonia and intermittent dyspnea two months after intubation due to epiglottic and vocal process granulomas. This is unusual in that multiple granulomas were found in the posterior glottis and supraglottis after short-term intubation. Our objective was to determine if there are risk factors for developing persistent post-intubation sequelae, including the delayed presentation and unusual location of post-intubation granulomas in our case. Study design: Case report and systematic literature review. Methods: Pubmed database, which is inclusive of MEDLINE, was used to perform a literature review with the search terms ((pediatric OR children OR neonatal OR infant) AND (laryngeal OR supraglottic) AND intubation AND (granuloma OR injury OR complication)). Only English language results were reviewed. Titles and abstracts from 379 results were reviewed. Full text was reviewed from all original studies which included human pediatric subjects and endoscopic examinations after endotracheal intubation. Results: In our case, laryngeal granuloma size reduced significantly after starting anti-reflux medications. The remainder was removed with laryngeal microdebrider with no recurrence at 3 weeks and 2.5 years post-operatively. Overall, 28 of the 379 studies reviewed identified evidence of laryngeal trauma due to intubation, however only 6 studies documented any type of supraglottic injury. Risk factors identified for developing post-intubation sequelae included intubation duration greater than 24 h; trauma to the larynx via various mechanisms including traumatic intubation, need for reintubation and tube changes, and increased movement while intubated; and presence of respiratory tract infection during intubation. Conclusion: Trauma to the larynx during intubation should be avoided to minimize post-intubation injury in pediatric patients, by using appropriate intubation protocols, endotracheal tube size, and adequate sedation.